Characteristics and Dissemination of Mosaic Penicillin-Binding Protein 2-Harboring Multidrug-Resistant Neisseria gonorrhoeae Isolates with Reduced Cephalosporin Susceptibility in Northern Taiwan - Huang, Chung-Ter (American Society for Microbiology (ASM), 2010)
Among 254 Neisseria gonorrhoeae isolates from a sexually transmitted infection (STI) clinic in northern Taiwan, 69 isolates were found to contain the mosaic penA (MA) gene and were associated with elevated cefixime and ceftriaxone MICs. Most of these MA gene-harboring isolates were also resistant to penicillin (71.4%) and ciprofloxacin (100%) and were from men who have sex with men (MSM) or from bisexual men (81.2%). Three major sequence types (ST835, ST2180, and ST2253) constituted 55.7% of these isolates. The major sequence types harboring the mosaic penA gene may represent major sexual networks responsible for the emergence/introduction and the spread of the multidrug-resistant clones in Taiwan.